1991
DOI: 10.1007/bf03189959
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of dipyridamole-β-cyclodextrin complex in healthy volunteers after single and multiple doses

Abstract: Dipyridamole is a well known anti-aggregating agent characterized by poor water solubility as well as scant and variable bioavailability. Recently, the compound was complexed with beta-cyclodextrin forming a molecular encapsulation resulting in better oral absorption and stronger biological activities in animals. In the present study, a randomized double blind cross-over comparison between dipyridamole-beta-cyclodextrin complex (dip-beta-CD) and dipyridamole was performed in 12 healthy subjects after single (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Gastric pH related variability has been demonstrated in elderly patients81 and raised gastric pH significantly lowers the oral absorption of the drug 82. Dosing as a cyclodextrin formulation helps to reduce variability and increased bioavailability 83. In addition, the use of acidifying agents in an extended release formulation has been used to improve the pharmacokinetic variability 49, 82.…”
Section: Results‐selected Example Drugsmentioning
confidence: 99%
“…Gastric pH related variability has been demonstrated in elderly patients81 and raised gastric pH significantly lowers the oral absorption of the drug 82. Dosing as a cyclodextrin formulation helps to reduce variability and increased bioavailability 83. In addition, the use of acidifying agents in an extended release formulation has been used to improve the pharmacokinetic variability 49, 82.…”
Section: Results‐selected Example Drugsmentioning
confidence: 99%
“…While these reports will not be extensively reviewed here, the subject of each publication will be addressed for the reader's information. Ricevuti et al 157 investigated the pharmacokinetics in healthy volunteers of dipyridamole and its -CD complex following single and multiple dosing and found better bioavailability from the complex. Yusuff et al 158 observed improved spironolactone bioavailability from a -CD complex and a micronized powder versus the commercial product, Aldactone.…”
Section: Oral Applications Of Cyclodextrinsmentioning
confidence: 98%
“…The target dosing strategy was to scale down to the clinical dose administered with a glass of water (i.e., 75, 200, and 200 mg for dipyridamole, ketoconazole, and itraconazole, respectively, with 250 mL water) [22][23][24]. For the biphasic experiments, since 40 mL of aqueous medium was used, the dipyridamole, ketoconazole and itraconazole doses were estimated to be 12, 32, and 32 mg, respectively.…”
Section: Dose Selectionmentioning
confidence: 99%